Urban Dynamics in Semarang City: A Study of Livable Cities - Fahdian, Achmad Tsani; Irawan, Yohanes Kurnia (Universitas Islam Sultan Agung Semarang, 2024)
This study explores sanitation issues in urban Semarang in the context of achieving a Livable City, particularly concerning sanitation waste directly discharged into drains and rivers. In collaboration with the Semarang City Government, this research piloted the Livable City Framework (LCF) as a rapid assessment methodology for city suitability. The research aims to identify livable areas that are performing well, which will be developed into sanitation investments, especially in neighborhoods traversed by the SPALD-T route. A mixed-method research approach was employed, utilizing two main instruments: web surveys and in-depth interviews. Research findings indicate strong social capital in Semarang, yet the ability to influence decisions remains low, indicating the need for increased education and community empowerment. Physical capital scores vary, with investments in public spaces needing attention to distribute development benefits evenly. Human and natural capital show potential for improvement, while some neighborhoods such as Kudu, Kalibanteng Kidul, and Kalipancur receive low scores and require further analysis and community engagement. This research provides a deep understanding of the complexity of urban development processes and emphasizes the need for cross-sector collaboration to achieve a Livable City